Desain Platform Smart Office pendukung Protokol Kesehatan Covid-19 bagi Pekerja - Muniaga Ivander (Jurnal Sistem Cerdas, 2021)
The Covid-19 pandemic has caused drastic changes in the economic world, such as household consumption, demand and supply patterns, job dynamics, and management crises in various organizations both government and private that force workers to work from home (work from home). . The spread of the virus has yet to show signs of ending with an increasing trend of new cases and confirmed deaths. Mobility or population movement is one of the factors that influence economic improvement in an area, this is what forces the government to adopt a policy of loosening the status of social restrictions in various regions so that the social and economic conditions in society do not fluctuate. Until an effective vaccine is found, the spread of Covid-19 will continue to increase sharply as long as social and economic activities are still carried out in the community, with these various obstacles, the new normal is a realistic step. Formal sector workers, especially those who work in office areas, have a high risk of being exposed to Covid-19. To protect workers, the government issued SE Ministry of Health HK.02.01 / MENKES / 335/2020 regarding the protocol for preventing the spread of Covid-19 in the work area. However, the implementation of the protocol did not match expectations, seen from the increasing number of clusters for the spread of Covid-19 in office areas since the relaxation of social restrictions. Although various digital office platforms are available, the existence of a physical office is still considered very important in maintaining the integrity of an organization. This paper proposes a smart office platform design to support the implementation of the Covid-19 health protocol in office areas for formal sector workers. It is hoped that the design of this platform can provide support for both public and private organizations to continue to play an important role as a driving force of the economy through activities in offices while still paying attention to the health of their workers